2022
DOI: 10.3389/fpsyt.2021.774063
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Engaged in Radicalisation and Terrorism: A Dimensional and Categorical Assessment

Abstract: Since 2010 and the founding of the Islamic State, the radicalisation phenomenon in Europe has involved more adolescents and converts to Islam than in previous Islamist terrorist group movements (e.g., Al-Qaeda). In most cases, these adolescents are “homegrown terrorists,” a challenging difference, as they are in confrontation with their home and societal environment. As a new and emerging phenomenon, radicalisation leads to many questions. Are empathic capacities altered? Are they presenting psychiatric pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Of these, five studies reported on diagnosed disorder (Bronsard et al, 2022; Capellan, 2015; Dhumad et al, 2020; Liem et al, 2018; Lyons & Harbinson, 1986), five report rates of psychological problems (Capellan & Anisin, 2018; Capellan et al, 2019; Capellan, 2015; Kupper & Meloy, 2021; Liem et al, 2018), and one reported on suspected disorder (Horgan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, five studies reported on diagnosed disorder (Bronsard et al, 2022; Capellan, 2015; Dhumad et al, 2020; Liem et al, 2018; Lyons & Harbinson, 1986), five report rates of psychological problems (Capellan & Anisin, 2018; Capellan et al, 2019; Capellan, 2015; Kupper & Meloy, 2021; Liem et al, 2018), and one reported on suspected disorder (Horgan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Excluding Bakker's (2006) sample of 242 individuals, less than 50 individuals were recruited to the other studies (Bronsard et al, 2022 n = 15; Lyons & Harbinson, 1986 n = 47; Merari et al, 2010 n = 41 (all samples); Merari & Ganor, 2020 n = 39). Both papers from Merari focused on Palestinian terrorism and invovled interviews with incarcerated terrorists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the marginal aspect of radicalization and the lack of publications offering a psychopathological perspective on radical conduct among adolescents justify this choice. It would be interesting to extend the present research through other studies that create a dialogue between public health studies ( 64 67 ), investigations using standardized scales in medium-sized samples of adolescents who are “at risk of radicalization” or who have become “radicalised” ( 26 , 68 ), and studies with a psychopathological perspective based on concrete case reports ( 28 , 29 , 32 , 33 ).…”
Section: Limitationsmentioning
confidence: 99%